A geoprocessing workflow system for environmental monitoring and integrated modelling. (July 2015) - Yue, Peng; Zhang, Mingda; Tan, Zhenyu
Abstract: Environmental information infrastructure benefits from mainstream information technologies including workflow and service technologies. These technologies allow distributed geoprocessing algorithms, models, data, and sensors to be accessed through Web Services, which later can be chained together to support environmental monitoring and integrated modelling. Existing approaches on integrated environmental modelling, such as OpenMI, have advantages in enabling interoperability between modelling components. It is possible to integrate both of them to take the best from both approaches. The paper introduces the design and implementation of a geoprocessing workflow tool, named GeoJModelBuilder, which is able to integrate interoperable Sensor Web, geoprocessing services, and OpenMI-compliant model components into workflows. In this way, sensors, data, geoprocessing functions, and models could be integrated in a flexible, reusable, interoperable, and user-friendly way. The system has been published as an open source software and illustrated in cases on environmental monitoring and integrated modelling. Highlights: Geo-enabled workflow tool by integrating interoperable Sensor Web, and geoprocessing services, and OpenMI. Event-driven workflows for "active" environmental monitoring. An open source implementation of the geoprocessing workflow tool.